Bimekizumab efficacy and safety in moderate to severe plaque psoriasis (BE READY): a multicentre, double-blind, placebo-controlled, randomised withdrawal phase 3 trial. Issue 10273 (6th February 2021) - Gordon, Kenneth B; Foley, Peter; Krueger, James G; Pinter, Andreas; Reich, Kristian; Vender, Ronald; Vanvoorden, Veerle; Madden, Cynthia; White, Katy; Cioffi, Christopher; Blauvelt, Andrew
Summary: Background: Bimekizumab is a monoclonal IgG1 antibody that selectively inhibits interleukin (IL)-17F in addition to IL-17A. This study investigated the efficacy and safety of bimekizumab in patients with moderate to severe plaque psoriasis, the effects of treatment withdrawal, and two maintenance dosing schedules over 56 weeks. Methods: BE READY was a phase 3, multicentre, randomised, double-blind, placebo-controlled trial done at 77 sites (hospitals, clinics, private doctor's practices, and dedicated clinical research centres) in nine countries across Asia, Australia, Europe, and North America. Adult patients aged 18 years or older with moderate to severe plaque psoriasis were stratified by region and previous biologic exposure, and randomly assigned (4:1) to receive bimekizumab 320 mg every 4 weeks or placebo every 4 weeks by use of interactive response technology. Coprimary endpoints were the proportion of patients achieving 90% or greater improvement from baseline in the Psoriasis Area Severity Index (PASI90) and the proportion of patients achieving a score of 0 (clear) or 1 (almost clear) on the five-point Investigator's Global Assessment (IGA) scale at week 16 (non-responder imputation). Bimekizumab-treated patients achieving PASI90 at week 16 were re-allocated (1:1:1) to receive bimekizumab 320 mg every 4 weeks, every 8 weeks, or placebo for weeks 16–56. Efficacy analyses were done in the intention-to-treat population; the safety analysis set comprised all patients who received at least one dose of study treatment. This trial is registered with ClinicalTrials.gov (NCT03410992 ), and is now completed. Findings: Between Feb 5, 2018, and Jan 7, 2020, 435 patients were randomly assigned to receive either bimekizumab 320 mg every 4 weeks (n=349) or placebo every 4 weeks (n=86). Coprimary endpoints were met: at week 16, 317 (91%) of 349 patients receiving bimekizumab 320 mg every 4 weeks achieved PASI90, compared with one (1%) of 86 patients receiving placebo (risk difference 89·8 [95% CI 86·1–93·4]; p<0·0001); and 323 (93%) of 349 patients receiving bimekizumab 320 mg every 4 weeks achieved an IGA score of 0 or 1 versus one (1%) of 86 patients receiving placebo (risk difference 91·5 [95% CI 88·0–94·9]; p<0·0001). Responses were maintained through to week 56 with bimekizumab 320 mg every 8 weeks and every 4 weeks. Treatment-emergent adverse events in the initial treatment period (up to week 16) were reported in 213 (61%) of 349 patients receiving bimekizumab 320 mg every 4 weeks and 35 (41%) of 86 patients receiving placebo every 4 weeks. From week 16 to week 56, treatment-emergent adverse events were reported in 78 (74%) of 106 patients receiving bimekizumab 320 mg every 4 weeks, 77 (77%) of 100 patients receiving bimekizumab 320 mg every 8 weeks, and 72 (69%) of 105 patients receiving placebo. Interpretation: Bimekizumab showed high levels of response, which were durable over 56 weeks, with both maintenance dosing schedules (every 4 weeks and every 8 weeks). Moreover, bimekizumab was well tolerated, with no unexpected safety findings. Data presented here further support the therapeutic value of bimekizumab and inhibition of IL-17F in addition to IL-17A for patients with moderate to severe plaque psoriasis. Funding: UCB Pharma.